2014
DOI: 10.1007/s11357-014-9627-2
|View full text |Cite
|
Sign up to set email alerts
|

In-depth analyses unveil the association and possible functional involvement of novel RAD51B polymorphisms in age-related macular degeneration

Abstract: The contribution of DNA damage to the pathogenesis of age-related macular degeneration (AMD) has been reported. Recently, a genomewide association study detected the association of a single-nucleotide polymorphism (SNP) in RAD51B (rs8017304 A>G) with AMD. RAD51B is involved in recombinational repair of DNA double-strand breaks. We analyzed RAD51B influence on AMD using two cohorts from Caucasian and Han Chinese populations. The Caucasian set replicated the rs8017304 A>G association and revealed two novel AMD-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…The study group demographics are summarized in Table 1 . Participant selection and clinical evaluation have been previously defined [ 17 20 ]. AMD cases were all in advanced stages and the controls presented either no drusen or fewer than 5 small drusen (<63 µm in diameter) and no signs of other retinal diseases, including but not limited to high myopia, retinal dystrophies, central serous retinopathy, vein occlusion, diabetic retinopathy, or uveitis.…”
Section: Methodsmentioning
confidence: 99%
“…The study group demographics are summarized in Table 1 . Participant selection and clinical evaluation have been previously defined [ 17 20 ]. AMD cases were all in advanced stages and the controls presented either no drusen or fewer than 5 small drusen (<63 µm in diameter) and no signs of other retinal diseases, including but not limited to high myopia, retinal dystrophies, central serous retinopathy, vein occlusion, diabetic retinopathy, or uveitis.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence of the pathogenic role of IL‐17A in AMD without a known genetic component led us to search for SNPs in IL‐17A that influence the development of AMD in our Caucasian NEI cohort [Tuo et al, ; Ardeljan et al, ; Chu et al, ]. Out of six SNPs tested, we found evidence of a single SNP, rs7747909, in the 3′UTR of IL‐17A that associates with AMD with a dominant logistic model.…”
Section: Discussionmentioning
confidence: 86%
“…Chu et al analyzed RAD51B influence on AMD using two cohorts from Caucasian and Han Chinese populations, as well. Scientists identified two new SNPs in RAD51B (rs17105278 and rs4902566) and confirmed the association between rs8017304 and AMD development in Caucasians [37], suggesting a significant role of RAD51B associated with DNA damage/DNA repair mechanism in AMD pathogenesis.…”
Section: Discussionmentioning
confidence: 93%
“…Also, literature review explains that risk alleles at RAD51B rs8017304, rs13081855 near COL8A1/FILIP1L locus, and rs3812111 in COL10A1 are associated with a greater risk for advanced AMD development [25]. Other three GWAS proved RAD51B gene association with AMD as well [26, 37, 38]. Seddon et al conducted a 12-year follow-up study of 2765 individuals and revealed that RAD51B (HR: 0.8; 95% CI: 0.60-0.97, p = 0.03) was significantly related to AMD progression [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation